Comparison of Conventional and Newer Iron Preparations for the Treatment of Iron Deficiency Anaemia in Children - Asmat Parveen , Naima Fazil Raja , Imran Mehmood Khan , Hijab Shaheen , Muhammad Imran , Rizwan Shafeeq Ahmed (Journal of Rawalpindi Medical College, 2020)
Introduction: Commonly used iron salt, ferrous sulphate for the treatment of iron deficiency anemia, has several gastrointestinal side effects. Nowadays new iron salts such as ferrous bisglycinate are marketed with claims of raising hemoglobin faster with fewer gastrointestinal side effects. Objective: To compare the efficacy of ferrous sulphate with ferrous bisglycinate for the treatment of iron deficiency anemia in children. Methods: This randomized controlled trial was carried out at Children Hospital, PIMS, Islamabad from July 2015 to June 2016. A total of 136 children were selected through systematic sampling and randomized into 2 groups using a computer-generated table of random numbers; ferrous sulphate as group 1 and ferrous bisglycinate as group 2. Clinical outcome was assessed on the basis of a mean increase in hemoglobin after 12 weeks of therapy in both groups. The data was entered and analyzed using SPSS version 20. Results: The baseline characteristics i.e. mean age, mean hemoglobin levels were similar in both study groups. After 12 weeks of treatment, the mean increase in hemoglobin was 1.8 ±1.59 g/dl in ferrous sulphate group as compare to 2.5 ±1.31g/dl in ferrous bisglycinate group showing the higher level of rising with ferrous bisglycinate than ferrous sulphate, P =0.0033. Conclusion: Newer iron preparation, ferrous bisglycinate is a better treatment option than conventional preparation of ferrous sulphate for increasing hemoglobin in iron deficiency anemia in children.